Eksistensi Home Industri Kerajinan Anyaman Bambu di Heuleut Leuwimunding Majalengka di Era Revolusi Industri 4.0 - Barnawi Barnawi (IAI Bunga Bangsa Cirebon, 2019)
This research is focused on the home industry of woven bamboo crafts in the village of Heuleut Leuwimunding Majalengka in 2019. The aspect studied is the objective conditions of the existence of woven bamboo crafts in the midst of the industrial revolution 4.0. This study aims to describe the existence of the bamboo handicraft home industry in the village of Heuleut Leuwimunding, Majalengka in 2019 in the midst of the industrial revolution 4.0. This research is a qualitative research. This type of research was chosen because qualitative research is able to provide descriptive data in the form of written or spoken words from the behavior of the people being observed. So that in researching